Development of TIETGrid Portal Using Web services - Doad, Gurleen Kaur (My University, 2007)
Grid technology is designed to allow users seamless access to applications and services running on remote resources. Grids are becoming platforms for high-performance and distributed computing. Grids benefit users by permitting them to access heterogeneous resources, such as machines, data, people and devices that are distributed geographically and organizationally. Globus Toolkit4 has been widely adopted as a Grid technology solution for scientific and technical computing. It implements web services mechanisms for building distributed systems. Web Services are the software components that have emerged as a popular standards-based framework for accessing network applications. Since majority of the grid applications are research-oriented, so there is need to provide a userinterface that does not involve much about grid programming. This thesis describes an approach to building grid services based on the premise that users who wish to access and run these services prefer to do so without becoming experts on grid technology. These services are visible to the users and to resource providers through a family of Grid portal components that can be used to configure, launch, and monitor complex applications in the scientific language of the end user. The work done as a part of the thesis involves developing a web service and deploying it in the GT4 container. This is followed by development of a TIET grid portlet that provides a user-friendly interface to this service.
Keywords: Grid Architecture; Grid Portal; Globus Toolkit; Web Services